2019
DOI: 10.15252/emmm.201809423
|View full text |Cite
|
Sign up to set email alerts
|

Repeat‐associated non‐ AUG translation in C9orf72‐ ALS / FTD is driven by neuronal excitation and stress

Abstract: Nucleotide repeat expansions (NREs) are prevalent mutations in a multitude of neurodegenerative diseases. Repeat‐associated non‐AUG (RAN) translation of these repeat regions produces mono or dipeptides that contribute to the pathogenesis of these diseases. However, the mechanisms and drivers of RAN translation are not well understood. Here we analyzed whether different cellular stressors promote RAN translation of dipeptide repeats (DPRs) associated with the G4C2 hexanucleotide expansions in C9orf72, the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 70 publications
9
100
0
Order By: Relevance
“…Recent mechanistic studies on RAN translation clearly indicate that cellular stress is another trigger for this non-canonical mode of protein synthesis. It has been reported that RAN translation of GGGGCC and CGG repeats is enhanced by diverse stress stimuli [26,27,29,36]. Our results are consistent with these data and indicate that RAN translation of ATXN3-associated repeat expansion sequences can also be driven by ISR.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Recent mechanistic studies on RAN translation clearly indicate that cellular stress is another trigger for this non-canonical mode of protein synthesis. It has been reported that RAN translation of GGGGCC and CGG repeats is enhanced by diverse stress stimuli [26,27,29,36]. Our results are consistent with these data and indicate that RAN translation of ATXN3-associated repeat expansion sequences can also be driven by ISR.…”
Section: Discussionsupporting
confidence: 92%
“…The core event of ISR is phosphorylation of the α subunit of eIF2, which leads to global protein synthesis attenuation accompanied by the induction of alternative mechanisms of translation initiation of selected mRNAs [61][62][63][64]. Recently, it has been reported that RAN translation at CGG and GGGGCC repeats is enhanced by ISR activation [26,27,29,36]. To examine whether this phenomenon can also occur in SCA3, cells transfected with selected RAN constructs (78/32-115CAG, 45/32-110CAG and 33/32-119CAG) were additionally exposed for 8 h to thapsigargin (TG), which causes endoplasmic reticulum (ER) stress, or to sodium arsenite (SA), which induces oxidative stress.…”
Section: Cellular Stress Enhances Sca3 Ran Translation Of the Cag Repmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, expanded repeats in ALS/FTD may be pathogenic through a double‐hit mechanism where the suboptimal autophagy due to C9ORF72 reduced expression may enhance the accumulation and toxicity of DPR proteins expressed under their natural sequences. These results are reminiscent of stress conditions that increase expression and toxicity of DPR proteins (Green et al , ; Cheng et al , ; Sonobe et al , ; Westergard et al , ). Our results are also consistent with the decreased expression of C9ORF72 that synergizes the toxicity of expanded G4C2 repeats in C9‐BAC transgenic mice (Shao et al , ) or that enhances the toxicity of DPR proteins expressed under artificial ATG start codons in neurons differentiated from C9‐iPS cells (Shi et al , ).…”
Section: Discussionmentioning
confidence: 92%
“…When undergoing the integrated stress response, cells commonly reduce canonical translation. In response to the presence of oxidative stress, cells with the C9orf72 HRE increase levels of non-canonical RAN translation of DRPs (Figure 2) (Westergard et al, 2019). In order to do so, initiation factors including eIF2α are phosphorylated, which has the effect of reducing the initiation of canonical translation, ultimately increasing RAN translation, although the mechanism by which RAN translation efficiency is altered has not yet been determined (Cheng et al, 2018).…”
Section: Oxidative Stress and Ran Translationmentioning
confidence: 99%